2019
DOI: 10.1002/adom.201900823
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Silicon Nanomembrane in a Tubular Geometry for Enhanced Photodetection

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adom.201900823. Silicon NanomembraneThe recent advances in 3D mesostructures have given rise to a number of intriguing devices that exhibit unique features, which have broad applications in flexible electronics, [1] photonics, [2,3] mechanics, [4] and biomedicine. [5] Among various fabrication techniques, rolled-up nanotechnology is an innovative method that constructs 3D tubular micro/nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…[14] The large-scale integration using rollingbased direct-transfer printing method has paved the way to mass produce these high-performance flexible and hybrid devices. [15] Broadband membrane photodetectors (PDs) are among the successfully implemented devices achieved using multiple materials including Si, [16,17] Ge, [18][19][20] SiGe, [21] InP, [22] InGaAs, [23] and Sb-based superlattices. [10,24] However, while these devices mainly operate at near infrared (NIR) and short-wave infrared (SWIR) wavelengths or at a longer THz wavelengths, developing membrane PDs operating in the mid-infrared (MIR) range has been severely limited by the lack of suitable material systems.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The large-scale integration using rollingbased direct-transfer printing method has paved the way to mass produce these high-performance flexible and hybrid devices. [15] Broadband membrane photodetectors (PDs) are among the successfully implemented devices achieved using multiple materials including Si, [16,17] Ge, [18][19][20] SiGe, [21] InP, [22] InGaAs, [23] and Sb-based superlattices. [10,24] However, while these devices mainly operate at near infrared (NIR) and short-wave infrared (SWIR) wavelengths or at a longer THz wavelengths, developing membrane PDs operating in the mid-infrared (MIR) range has been severely limited by the lack of suitable material systems.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of the monolayer graphene microtubes is based on rolling-up nanotechnology. 20 First, polycrystalline monolayer graphene was grown on a 4-in. Ge(111) wafer through chemical vapor deposition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another kind of 3D mesostructure was fabricated using an innovative rolled-up nanotechnology to form 3D tubular micro/nanostructures by rolling ultra-thin Si NMs. Xu et al demonstrated 3D tubular Si photodetectors with enhanced broadband photodetection and responsivity using self-rolling ultra-thin Si NMs [137]. This unique 3D structured device and its performance are presented in Fig.…”
Section: Stretchable Electronicsmentioning
confidence: 99%